2014
DOI: 10.1007/s10681-014-1245-7
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress response of wheat–barley addition lines carrying chromosomes from the winter barley “Manas”

Abstract: The salt stress responses of wheat-barley addition lines (2H, 3H, 3HS, 4H, 6H, 7H and 7HL) were compared to those of the parental genotypes wheat cv. Asakaze and barley cv. Manas and two other wheat genotypes [Chinese Spring (CS) and Mv9kr1] during germination and in young plants grown in hydroponic culture with or without salt treatment. Among the wheat genotypes frequently used for interspecific hybridization, Asakaze possesses relatively high salt tolerance, as indicated by the less pronounced reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
(51 reference statements)
4
30
0
Order By: Relevance
“…without or with 500 mM NaCl, respectively). These results are in accordance with earlier findings where comparative analysis revealed that salt-tolerant genotypes are characterised by higher osmotic adjustment ability (Darko et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…without or with 500 mM NaCl, respectively). These results are in accordance with earlier findings where comparative analysis revealed that salt-tolerant genotypes are characterised by higher osmotic adjustment ability (Darko et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Changes in Na + uptake or transport processes are among the mechanisms which may contribute to better salt tolerance in cereals (Saqib et al, 2011;Darko et al, 2015). In the present experiments, there was no difference in the leaf Na content of salt-acclimated and non-acclimated plants after exposure to high NaCl, indicating that salt acclimation did not significantly modify Na transport to the shoots, and suggesting that, under these experimental conditions, protective mechanisms other than altered Na transport to the leaves must be responsible for the reduced level of damage symptoms in the salt-acclimated plants.…”
Section: Discussionmentioning
confidence: 99%
“…Manas cultivars in order to increase the allelic variation of wheat (Molnár-Láng et al 2012). It has recently been reported by Darkó et al (2015), that among the added barley chromosomes tested (2H, 3H, 4H, 6H, 7H), the 7H addition line has elevated salt tolerance as compared to the wheat parent, and that the salt tolerance of the 7H addition line is associated with elevated osmotic adjustment capacity, similar to that found in Manas. However, except for a short preliminary study showing that increasing salt concentrations caused a less pronounced decline in net photosynthesis in the wheat (Asakaze)barley (Manas) 7H addition line (7H add) than in the parental variety Asakaze (Dulai et al 2010), the photosynthetic responses of this line, focusing to the role of photoprotective mechanisms and electron transport processes connected to PSII and PSI under salt treatment have not yet been studied in detail.…”
Section: Introductionsupporting
confidence: 54%
“…These results show that Manas and the 7H add were able to maintain their water status at a level similar to that of Asakaze without intense stomatal closure. This suggests that an efficient osmoregulation mechanism exists in these genotypes, as also demonstrated by Darkó et al (2015). Teulat et al (1998) also suggested that the 7H homoeologous chromosome played a role in osmotic adjustment in barley.…”
Section: Discussionmentioning
confidence: 65%
“…Hordeum marinum (2n = 14) is a diploid form of Hordeum genus with a basic chromosome number of x = 7 and four major groups H, I, X and Y. The long arm of chromosome 7H may be responsible for the improved salt tolerance (Darko et al 2015).…”
Section: Introductionmentioning
confidence: 99%